Dynamics of internet routing information. - Chinoy, Bilal (Computer communication review.)
The Internet is a complex mesh of networks that use a common suite (TCP/IP) of networking protocols. A key feature of the Internet is that all of these constituent networks are interconnected, thereby providing system wide communication. The magnitude and pattern of the flow of routing information directly represents the connectivity stability of the Internet. The NSFNET backbone network provides transit services to a large portion of the global Internet and maintains routing tables reflecting this current connectivity. These routing tables are constantly updated based on information received by the attached networks. This paper investigates the dynamics of routing information flow as presented to the NSFNET backbone network.